Definition of the energy performance requirements in rehabilitation projects - Almeida, Manuela Guedes de (2012)
Building rehabilitation is essential to achieve the targets defined by the EPBD-recast regarding energy efficiency, reduction of carbon emissions and use of on-site renewable energy sources. To propose an effective building rehabilitation it is necessary to study the best combination of available options in terms of construction solutions, technical building systems (hot water, ventilation, heating, cooling and lighting), their cost, but also their impact on the thermal and acoustic comfort and indoor air quality of the building. Also, the definition of the cost-optimal level is essential, which is the minimum lifecycle cost (including investment costs, maintenance and operating costs, energy costs, earnings from energy produced and disposal costs) of each individual measure. In this work the multi-criteria decision analysis method ELECTRE III will be applied to balance all these aspects, during the design phase of a refurbishment project, in order to assist the design team on the selection of construction solutions and technical building systems. A simple case study is presented to demonstrate the feasibility of this approach in what concerns the definition of the energy performance requirements (e.g. thickness of insulation and efficiency of the heating system/air-conditioning system etc.), of a rehabilitation project. In this example several retrofit alternatives were studied, their implementation could lead to the reduction of the energy needs of the building from 13% to 83%. With this approach it was also possible to identify the alternative with the best global performance considering the investment costs, energy needs, indoor air quality, thermal comfort, and CO2 emissions.